Gene Therapy: The Molecular Bandage for Treating Genetic Disorders - Karim, Md Manjurul (Anwer Khan Modern Medical College Journal, 2012)
The concept of gene therapy involves the transfer of genetic material into a cell, tissue, or whole organ, with a view to curing a disease or at least improving the clinical status of a patient. Much of its success relies heavily on the development of an effective delivery system that is capable of efficient gene transfer in a variety of tissues, without causing any associated pathogenic effects. Viral vectors currently offer the best choice for efficient gene delivery, what has been discussed in this review article. Their performance and pathogenecity has been evaluated in animal models, and encouraging results form the basis for clinical trials to treat genetic disorders and acquired diseases. Despite some initial success in these trials, vector development remains a seminal concern for improved gene therapy technologies. DOI: http://dx.doi.org/10.3329/akmmcj.v3i1.10110 AKMMCJ 2012; 3(1): 24-27